Efeito do nível de atividade física nas concentrações da ADAM 10 em sujeitos com doença de Alzheimer e saudáveis - Barreto, Maria Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
It is known that physical activity can promote several changes in cognitive functions and today is regarded as a non-pharmacological form of treatment and prevention for Alzheimer's disease. One of the mechanisms that lead to these changes is the production of neurotransmitter uptake and which have a direct action on the central nervous system and, moreover, can be directly related to the modulation and production of biomarkers related to disease. Currently, the main postulates have recommended new diagnostic criteria and research in Alzheimer's disease (AD). Among the various examinations are biomarkers that currently are used solely for the purpose of research, but more and more are gaining space for clinical diagnosis. Among the biomarkers associated with AD there is a catalytic enzyme family of disintegrins and metalopeptidadse, ADAM 10 has among its various functions, the ability to cleave the amyloid precursor protein (APP) and promote the release of a substance and neurogenic neuroprotection to neurons. To elucidate this possible relationship between physical activity and the concentration of that specific enzyme, the study aimed to verify the effect of physical activity at concentrations of enzyme ADAM10 in healthy elderly with AD. The study included 29 healthy and 28 older people with AD. To check the level of physical activity using an accelerometer the elderly and answered the questionnaire Baecke modified for the elderly. In addition, a cognitive function screening test was also applied and evaluated the depressive symptoms of the subjects. By means of a blood collection ADAM10 concentrations are analyzed. Results and Conclusion: It was observed that in both groups the ADAM10 concentrations increased with increasing the physical activity level. There was a significant difference in the average level of physical activity, sedentary behavior, time of moderate / vigorous physical activity, Baeck questionnaire modified for the...

Sabe-se que a atividade física é capaz de promover várias alterações nas funções cognitivas e hoje em dia é tida como uma forma não farmacológica de tratamento e prevenção para a Doença de Alzheimer. Um dos mecanismos que levam a essas alterações é a produção e captação de neurotransmissores os quais possuem ação direta no sistema nervoso central e, além disso, podem ter relação direta com a modulação e produção de biomarcadores relacionados à doença. Atualmente, os principais postulados têm recomendado novos critérios de diagnóstico e pesquisa na Doença de Alzheimer (DA). Entre os vários exames realizados existem os biomarcadores que no momento são utilizados com finalidade exclusiva de pesquisa, mas que cada vez mais vêm ganhando espaço para diagnóstico clínico. Entre os biomarcadores relacionados com a DA existe uma enzima catalítica da família das desintegrinas e metalopeptidadse, a ADAM 10 que possui entre suas várias funções, a capacidade de clivar a proteína precursora de amilóide (APP) e promover a liberação de uma substância neurogênica e neuroprotetora aos neurônios. Para elucidar essa possível relação entre atividade física e a concentração dessa enzima específica, o objetivo do estudo foi verificar o efeito do nível de atividade física nas concentrações da enzima ADAM10 em idosos saudáveis e com DA. Participaram do estudo 29 hígidos e 28 idosos com DA. Para verificar o nível de atividade física os idosos utilizaram um acelerômetro e responderam ao questionário Baecke modificado para idosos. Além disso, foi aplicado um teste de rastreamento da função cognitiva e também, foram avaliados os sintomas depressivos dos sujeitos. Por meio de uma coleta sanguínea serão analisadas as concentrações de ADAM10. Resultados e Conclusão: Observou-se que nos dois grupos as concentrações de ADAM10 aumentavam conforme o aumento do nível de atividade física. Houve...
Keywords: Physical education and training; Educação fisica; Alzheimer, Doença de; Marcadores biologicos; Enzimas; Cognição na velhice; Exercícios físicos para idosos